1981
DOI: 10.1037/0278-7393.7.5.355
|View full text |Cite
|
Sign up to set email alerts
|

Linear separability in classification learning.

Abstract: Four experiments were performed to determine whether linearly separable categories are easier to learn than categories that are not linearly separable. Linearly separable categories are categories that can be perfectly partitioned on the basis of a weighted, additive combination of component information. Independent cue models (e.g., prototype theories) predict that, with average between-category similarity held constant, linearly separable categories will be easier to master. Relational coding models (e.g., t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
275
1
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(281 citation statements)
references
References 29 publications
4
275
1
1
Order By: Relevance
“…In fact, a demonstration that natural concept categories are commonly not linearly separable would be excellent evidence against the similarity view. Although it has been shown that certain non-linearly separable categories are as easy (or difficult) to learn as linearly separable ones (Medin and Schwanenflugel, 1981), I am aware of no direct evidence of this kind.…”
Section: Discussionmentioning
confidence: 85%
“…In fact, a demonstration that natural concept categories are commonly not linearly separable would be excellent evidence against the similarity view. Although it has been shown that certain non-linearly separable categories are as easy (or difficult) to learn as linearly separable ones (Medin and Schwanenflugel, 1981), I am aware of no direct evidence of this kind.…”
Section: Discussionmentioning
confidence: 85%
“…Although a lot of recent categorization research has focused on the need for models with more elaborate, mixed representations (Ashby, Alfonso-Reese, Turken, & Waldron, 1998;Erickson & Kruschke, 1998;Love, Medin, & Gureckis, 2004;, simple exemplar, prototype, and rule-based representations continue to be considered relevant, particularly in the context of research emphasizing different types of category learning and use (Markman & Ross, 2003;Yamauchi & Markman, 1998). Exemplar models have been widely shown to provide a better account of perceptual category learning than prototype or simple rule models (e.g., Medin & Schaffer, 1978;Medin & Schwanenflugel, 1981;Nosofsky, 1992). Evidence for simple rules continues to be found (e.g., Ashby et al, 1998;Erickson & Kruschke, 1998;Johansen & Palmeri, 2002;, but usually in conjunction with some other type of representation, such as exemplars or prototypes.…”
mentioning
confidence: 99%
“…A question of crucial importance, in this regard, concerns the constraints by which natural concepts are characterized. It would be hard to believe that human culture has passed on categories with a structure that is not coordinated with the constraints of human information processing (Medin & Schwanenflugel, 1981;Sperber, 2000).…”
mentioning
confidence: 99%